Novel fabrication technique for NiTi and TiN micro-structures by fem to second lasers. Issue 1 (June 2020) - Jithin, M A; Ganapathi, K L; Udayashankar, N K; Mohan, S
Abstract: NiTi shape memory alloy (SMA) thin films were deposited onto silicon substrate using pulsed DC magnetron sputtering technique. To obtain crystalline NiTi thin films has to be synthesized at higher temperatures (475 - 525) °C. This high temperature requirement restricts the ease in conventional lithographic procedures. The recent advancements in the laser micromachining lend their applications into the fabrication of miniaturized systems. The femtosecond lasers (FSL) allow non-thermal processing of materials by ablation. This work focuses on the deposition and fabrication of NiTi (≈1.5 μm. thick) and titanium nitride (TiN ≈0.3 μm. thick) thin films based miniaturized systems by femtosecond laser bulk micromachining. The NiTi and TiN microstructures were release by bottom silicon etch using reactive ion etching chlorine chemistry (RIE-Cl).